The segmental-based approach during anatomy coursework presents better results than the systems-based approach - Thalles Guilarducci Costa; Mario Hebling Campos; Ana Claudia Ferreira Barros; Marilia Santos Andrade; Rodrigo Luiz Vancini; Ricardo Borges Viana; Thomas Rosemann; Katja Weiss; Beat Knechtle; Claudio Andre Barbosa de Lira (BMC Medical Education)
Abstract Traditionally, there are two pedagogical approaches to teaching human anatomy. The first is the systems-based approach (study of body systems – bones, muscles, organs – separately) gross anatomy courses and the second is the segmental-based approach (study of body segments – upper and lower limbs and trunk – separately); both are highly recommended. However, to the best of our knowledge, less is known about academic performance comparing the two approaches. Thus, in this study, we evaluate undergraduate students’ academic performance in human anatomy courses using systems- or segmental approaches, also, evaluate attendance, the impact of missing class on performance, the course evaluations (specific to the professor) and the student perceptions of the different coursework. The final grade and class attendance of 141 undergraduate students, from the sports and exercise science program, undertaking the anatomy course, were evaluated. Seventy students participated in the systems-based gross human anatomy approach (SYS), and 71 students participated in the segmental-based gross human anatomy approach (SEG). Students in SEG (median [interquartile range (IQR]: 7.3 [2.0]) performed better academically, with higher final grades (U = 1,804.5, p = 0.005; rB = 0.274 [95% confidence interval (CI): 0.09–0.44]; medium effect) than SYS (median [IQR]: 6.6 [1.6]). SEG had higher class attendance (median [IQR]: 60 [8]) than SYS (median [IQR]: 60 [7]; U = 1,919.5, p = 0.015; rB = 0.228 [95%CI: 0.040–0.399]; small effect). Students in SEG rated the professor’s performance more highly than SYS (U = 78.0, p = 0.001; rB = 0.616 [95%CI: 0.332–0.797]; large effect). The segmental-based gross human anatomy approach leads to better academic performance and higher attendance in the gross anatomy course than SYS.